2012
DOI: 10.1038/srep00916
|View full text |Cite
|
Sign up to set email alerts
|

PMA-induced dissociation of Ku86 from the promoter causes transcriptional up-regulation of histamine H1 receptor

Abstract: Histamine H1 receptor (H1R) gene is up-regulated in patients with allergic rhinitis, and its expression level strongly correlates with the severity of symptoms. However, the mechanism underlying this remains unknown. Here we report the mechanism of H1R gene up-regulation. The luciferase assay revealed the existence of two promoter regions, A and B1. Two AP-1 and one Ets-1 bound to region A, while Ku86, Ku70, and PARP-1 bound to region B1. Ku86 was responsible for DNA binding and poly(ADP-ribosyl)ated in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…This observation is in agreement with the data showing that inhibition of PKC signaling by the pan PKC inhibitor GF109203X led to a significant increase in H 2 O 2 -induced PAR formation. Indeed, PKC has been previously shown to phosphorylate ARTD1 in vitro ( 38 ) and its inhibition resulted in increased PAR induction upon alkylation stress ( 37 ), while there are also studies that have reported a positive regulation of ARTD1 by PKCδ in response to histamine ( 39 , 75 ). Thus, reported studies so far have identified two seemingly opposing (positively and negatively), Ca 2+ -dependent and -independent regulatory mechanisms for PAR formation upon H 2 O 2 -induced oxidative stress within the PKC family of proteins in human primary fibroblasts as well as in murine NIH/3T3 cells and MEFs.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in agreement with the data showing that inhibition of PKC signaling by the pan PKC inhibitor GF109203X led to a significant increase in H 2 O 2 -induced PAR formation. Indeed, PKC has been previously shown to phosphorylate ARTD1 in vitro ( 38 ) and its inhibition resulted in increased PAR induction upon alkylation stress ( 37 ), while there are also studies that have reported a positive regulation of ARTD1 by PKCδ in response to histamine ( 39 , 75 ). Thus, reported studies so far have identified two seemingly opposing (positively and negatively), Ca 2+ -dependent and -independent regulatory mechanisms for PAR formation upon H 2 O 2 -induced oxidative stress within the PKC family of proteins in human primary fibroblasts as well as in murine NIH/3T3 cells and MEFs.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds also inhibit the phosphorylation of Tyr 311 on PKC δ (Mizuguchi et al. ; Hattori et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies showing the participation of Ku protein in the transcription regulation of cellular and viral genes [40,[78][79][80][81][82][83][84], and it is supposed that there is a specific mechanism of Ku-dependent regulation for each particular gene. Among the mechanisms proposed, there is no either involving the interaction of Ku with RNA, but we cannot completely rule out such a possibility.…”
Section: Interactions Of Ku With Protein Components Of the 7sk Ribonumentioning
confidence: 99%